Estimates vary but credible evidence points to gigaton-scale climate change mitigation potential of biochar - Zhe Han Weng; Annette L. Cowie (Communications Earth & Environment)
Abstract Biochar is a carbon dioxide (CO2) removal strategy that supports food security, sustainable land management and the circular economy. Nineteen published studies estimate global climate change mitigation potential of biochar at 0.03 to 11 Pg CO2 equivalent yr−1. Reconciling this range requires consideration of biochar science. Biochar systems durably sequester carbon, can reduce soil greenhouse gas (GHG) emissions, displace fossil fuel emissions through use of syngas, and avoid GHG emissions from residues. We reviewed the contributions to CO2 removal and GHG emissions reduction. Divergence between studies arises from differences in scope, definition of potential, and assumptions about biomass availability, biochar technologies and reference systems. Seven of the 19 studies reviewed relied one original study. Recent independent assessments estimate sustainable mitigation potential of biochar systems at 2.6-10.3 Pg CO2 equivalent yr−1. New assessments are needed, utilising integrated assessment models that incorporate latest understanding of biochar processes and feedstock availability.